Beyond connecting the dots: A multi-scale, multi-resolution approach to marine habitat mapping. (September 2021) - van der Reijden, Karin J.; Govers, Laura L.; Koop, Leo; Damveld, Johan H.; Herman, Peter M.J.; Mestdagh, Sebastiaan; Piet, Gerjan; Rijnsdorp, Adriaan D.; Dinesen, Grete E.; Snellen, Mirjam; Olff, Han
Highlights: Ecology-inclusive marine spatial planning requires accurate, detailed habitat maps. Biotic-based habitat maps represent benthic assemblages better than physiotope maps. The differences between faunal groups should be considered in marine habitat mapping. Anthropogenic activities are habitat-specific, and should be managed as such. Abstract: Conflicts of interests between economic and nature conservation stakeholders are increasingly common in coastal seas, inducing a growing need for evidence-based marine spatial planning. This requires accurate, high-resolution habitat maps showing the spatial distribution of benthic assemblages and enabling intersections of habitats and anthropogenic activities. However, such detailed maps are often not available because relevant biological data are scarce or poorly integrated. Instead, physiotope maps, solely based on abiotic variables, are now often used in marine spatial planning. Here, we investigated how pointwise, relatively sparse biological data can be integrated with gridded, high-resolution environmental data into informative habitat maps, using the intensively used southern North Sea as a case-study. We first conducted hierarchical clustering to identify discrete biological assemblages for three faunal groups: demersal fish, epifauna, and endobenthos. Using Random Forest models with high-resolution abiotic predictors, we then interpolated the distribution of these assemblages to high resolution grids. Finally, we quantified different anthropogenic pressures for each habitat. Habitat maps comprised a different number of habitats between faunal groups (6, 13, and 10 for demersal fish, epifauna, and endobenthos respectively) but showed similar spatial patterns for each group. Several of these 'fauna-inclusive' habitats resembled physiotopes, but substantial differences were also observed, especially when few (6; demersal fish) or most (13; epifauna) physiotopes were delineated. Demersal fishing and offshore wind farms (OWFs) were clearly associated with specific habitats, resulting in unequal anthropogenic pressure between different habitats. Natura-2000 areas were not specifically associated with demersal fishing, but OWFs were situated mostly inside these protected areas. We thus conclude that habitat maps derived from biological datasets that cover relevant faunal groups should be included more in ecology-inclusive marine spatial planning, instead of only using physiotope maps based on abiotic variables. This allows better balancing of nature conservation and socio-economic interests in continental shelf seas.